Comorbidities, concomitant medications and potential drug‐drug interactions with interferon‐free direct‐acting antiviral agents in hepatitis C patients in Taiwan. Issue 11 (25th October 2018) - Liu, Chen‐Hua; Yu, Ming‐Lung; Peng, Cheng‐Yuan; Hsieh, Tsai‐Yuan; Huang, Yi‐Hsiang; Su, Wei‐Wen; Cheng, Pin‐Nan; Lin, Chih‐Lin; Lo, Ching‐Chu; Chen, Chi‐Yi; Chen, Jyh‐Jou; Ma, Qian; et al.
Summary: Background: While direct‐acting antivirals have been approved for treating hepatitis C, the guidelines highlight the importance of considering potential drug‐drug interactions between DAAs and concomitant medications. Aim: To assess comorbidity prevalence, concomitant medication use and potential drug‐drug interactions between DAAs and concomitant medications for hepatitis C patients in Taiwan. Methods: This cross‐sectional study enrolled 822 patients from May to August 2016 in Taiwan. Patient demographics, comorbidities and concomitant medications were evaluated by physician surveys. Results: A total of 709 (86.3%) patients had ≥1 comorbidity; the most prevalent comorbidity categories were diseases of the digestive system (40.1%), circulatory system (38.7%) and endocrine/nutritional/metabolic diseases (35.2%). Elderly patients had more comorbidities. A total of 622 (75.7%) patients received ≥1 concomitant medication; the average number of concomitant medications was 3.2. The most common concomitant medication classes were cardiovascular (34.4%), gastrointestinal (25.7%) and central nervous system drugs (22.7%). Among patients without cirrhosis or with compensated cirrhosis, contraindications were most prevalent with paritaprevir/ritonavir/ombitasvir plus dasabuvir, daclatasvir/asunaprevir and glecaprevir/pibrentasvir (13.3%, 6.0% and 5.4% respectively), and least prevalent with sofosbuvir, sofosbuvir/daclatasvir, sofosbuvir/ledipasvir and sofosbuvir/velpatasvir (0.8%, 1.3%, 1.4% and 2.1% respectively). Sofosbuvir‐based regimens had no contraindications in patients with decompensated cirrhosis. Conclusion: Our population represented an elderly demographic, with a high prevalence of comorbidities and widespread use of concomitant medications. The potential drug‐drug interactions between these concomitant medications and DAA regimens differed, with the fewest potential interactions with sofosbuvir‐based regimens. Abstract : LINKED CONTENT This article is linked to Kawabe et al and Liu and Kao papers. To view these articles visit https://doi.org/10.1111/apt.15051 and https://doi.org/10.1111/apt.15065 .